Perceptions of green branding and identity building amongst small Finnish textile producers - Meurman, Maria (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The textile industry is one of the most polluting industries in the world. The amount of air and water pollution it causes puts a burden on the environment. There are companies who have taken the environmental and social aspects into account in the their production and chosen to operate in a green manner. This thesis studies how the phenomenon of green branding is seen from the perspectives of small Finnish textile companies. The theory used in this thesis has to do with green branding and identity building. The theory is used to analyze the results of the empirical findings. The main research question that the thesis aims to answer is how green branding is perceived within the Finnish textile industry. In order to answer the main research question, empirical data was collected from five relevant companies within the Finnish textile industry. The companies interviewed for the study were WST, Saana ja Olli, RCM, R-collection and Tiensivu. The study was conducted as a multiple case based study where multiple experts from green companies were interviewed. The experts were all owners or employees of companies that have a so-called green brand identity. The data was collected through semi-structured interviews, where the relevant experts from each company were interviewed either by themselves, in pairs or in groups. The data that was collected for this study was primary data, and the results of the study are mainly based on the experiences and opinions of the experts interviewed. The data collected does not cover the entire green textile industry within Finland, but study does however give a fairly comprehensive view of the phenomenon, as the textile industry in Finland is quite concise. The general findings of the study show that all experts from the companies interviewed agreed that a green brand identity does benefit their company in one way or the other. The findings also show contradictions with the older theory (eg. Charter et al. 1999, Pickett et al. 1995), and perhaps give a more modern view of the thoughts within the industry.

Tekstiiliteollisuus on yksi maailman eniten saastuttavimpia toimialoja ja sen aiheuttamat ilmansaasteet ja päästöt vesistöihin koettelevat ympäristöä jatkuvasti. Osa tekstiilialan yrityksistä on kuitenkin ottanut askeleen vihreämpään suuntaan ja keskittynyt toimimaan mahdollisimman ekologisesti ympäristöä kunnioittaen. Tässä pro gradu –tutkielmassa tarkastellaan vihreää brändäystä hyödyntäneiden, Suomessa toimivien pienten tekstiilialan yritysten kokemuksia Tutkielman teoria liittyy vihreään brändäämiseen ja brändi-identiteetin luomiseen. Teoriaa käytetään empiirisen aineiston analysoimiseen, joka on kerätty haastattelujen kautta. Tutkielmaan haastateltiin viittä vihreästi brändättyä Suomessa toimivaa yritystä; haastateltavina olivat WST, Saana ja Olli, RCM, R-collection, ja Tiensivu. Tutkimus toteutettiin multiple case tyyppisenä tutkimuksena, jossa haastateltiin tarkastellun alan erityisosaajia, Tutkimuksessani erityisosaajat olivat vihreästi brändättyjen yritysten omistajia tai työntekijöitä. Haastattelut toteutettiin puolistrukturoidusti ja yrityksen edustajia haastateltiin yrityskohtaisesti joko yksin, pareittain tai ryhmässä. Tutkimukseen kerätty aineisto on ensisijaista ja perustuu haastateltavien henkilöiden omiin kokemuksiin ja mielipiteisiin. Vihreä tekstiiliala on Suomessa vielä melko kehittymätön, joten kerätty aineisto antaa siitä melko kattavan kuvan. Keskeisimmät tutkimustulokset osoittavat haastateltavien kokeneen vihreän brändiidentiteetin tuoneen heidän yrityksilleen etua. Tutkimustulokset ovat osittain ristiriidassa vanhemman teorian kanssa (esim. Charter et al. 1999, Pickett et al. 1995), ja antavatkin ehkä hieman modernimman näkemyksien toimialasta nykypäivänä